Regulatory T cells in the mouse hypothalamus control immune activation and ameliorate metabolic impairments in high-calorie environments - Becker, Maike; Kälin, Stefanie; Neubig, Anne H.; Lauber, Michael; Opaleva, Daria; Hipp, Hannah; Salb, Victoria K.; Ott, Verena B.; Legutko, Beata; Kälin, Roland E.; Hippich, Markus; Scherm, Martin G.; et al. (Nature Communications, 2025)
The hypothalamus in the central nervous system (CNS) has important functions in controlling systemic metabolism. A calorie-rich diet triggers CNS immune activation, impairing metabolic control and promoting obesity and Type 2 Diabetes (T2D), but the mechanisms driving hypothalamic immune activation remain unclear. Here we identify regulatory T cells (Tregs) as key modulators of hypothalamic immune responses. In mice, calorie-rich environments activate hypothalamic CD4+ T cells, infiltrating macrophages and microglia while reducing hypothalamic Tregs. mRNA profiling of hypothalamic CD4+ T cells reveals a Th1-like activation state, with increased Tbx21, Cxcr3 and Cd226 but decreased Ccr7 and S1pr1. Importantly, results from Treg loss-of function and gain-of-function experiments show that Tregs limit hypothalamic immune activation and reverse metabolic impairments induced by hyper-caloric feeding. Our findings thus help refine the current model of Treg-centered immune-metabolic crosstalk in the brain and may contribute to the development of precision immune modulation for obesity and diabetes.
CRIS-Team Scopus Importer:2025-04-01